Respuesta :

Answer:

[tex]\Large \boxed{(5^{-2})^{-3}}[/tex]

Step-by-step explanation:

Applying the law of exponents : [tex](a^b)^c=a^{bc}[/tex]

[tex](5^4)^2 = 5^{4 \times 2} = 5^{8}[/tex]

[tex](5^{-2})^{-3}=5^{-2 \times -3}=5^6[/tex]

[tex](5^1)^5 =5^{1 \times 5}=5^5[/tex]

Answer:

[tex]\huge\boxed{Option \ B}[/tex]

Step-by-step explanation:

[tex]5^6[/tex] is equivalent to

=>   [tex](5^4)^2 = 5^{4*2} = 5^ 8[/tex]

=> [tex](5^{-2})^{-3} = 5^{-2*-3} = 5^6[/tex]          ← Correct

=> [tex](5^1)^5 = 5^{1*5} = 5^5[/tex]